Control over Near-Ballistic Electron Transport through Formation of Parallel Pathways in a Single-Molecule Wire - Aragonès, A.; Darwish, Nadim; Ciampi, Simone; Jiang, L.; Roesch, R.; Ruiz, E.; Nijhuis, C.; Díez-Pérez, I. (American Chemical Society, 2019)
This paper reports highly efficient coherent tunneling in single-molecule wires of oligo-ferrocenes with one to three Fc units. The Fc units were directly coupled to the electrodes, i.e., without chemical anchoring groups between the Fc units and the terminal electrodes. We found that a single Fc unit readily interacts with the metal electrodes of an STM break junction (STM = scanning tunneling microscope) and that the zero-voltage bias conductance of an individual Fc molecular junction increased 5-fold, up to 80% of the conductance quantum G0 (77.4 µS), when the length of the molecular wire was increased from one to three connected Fc units. Our compendium of experimental evidence combined with nonequilibrium Green function calculations contemplate a plausible scenario to explain the exceedingly high measured conductance based on the electrode/molecule contact via multiple Fc units. The oligo-Fc backbone is initially connected through all Fc units, and, as one of the junction electrodes is pulled away, each Fc unit is sequentially disconnected from one of the junction terminals, resulting in several distinct conductance features proportional to the number of Fc units in the backbone. The conductance values are independent of the applied temperature (-10 to 85 °C), which indicates that the mechanism of charge transport is coherent tunneling for all measured configurations. These measurements show the direct Fc-electrode coupling provides highly efficient molecular conduits with very low barrier for electron tunneling and whose conductivity can be modulated near the ballistic regime through the number of Fc units able to bridge and the energy position of the frontier molecular orbital.